Determination of epinephrine, norepinephrine and dopamine in human urine using high-performance liquid chromatography with coulometric detection - Drábková, Petra; Bencová, Soňa; Štramová, Xenie; Žáková, Pavla; Kanďár, Roman (University of Pardubice, 2013)
A relatively simple method for the simultaneous determination of epinephrine, norepinephrine and dopamine in urine is presented. We have used a highperformance liquid chromatography (HPLC) with coulometric electrochemical detection. The urine samples pretreated by a solid-phase extraction were injected directly into the HPLC system and were eluted isocratically on a Discovery HS C18, 250×4 mm i.d., 5 μm, analytical column. The analytical performance of this method is satisfactory: the intra-assay and inter-assay coefficients of variation were below 10 %. Quantitative recoveries from spiked urine samples were in the intervals of 78.2-88.0 % for epinephrine, 80.0-93.0 % for norepinephrine, and 96.4-107.2 % for dopamine. The linear range is 2-200 μg l–1, with a detection limit of 0.6 μg l–1 (signal-to-noise ratio = 3) for epinephrine, 5-500 μg l–1, with a detection limit of 1.5 μg l–1 for norepinephrine, and 20-2000 μg l–1, with a detection limit of 6 μg l–1 for dopamine.